2017
DOI: 10.1002/jlb.4a0917-363rr
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of BCG Hip1 protease enhances dendritic cell and CD4 T cell responses

Abstract: Dendritic cells (DCs) play a key role in the generation of CD4 T cell responses to pathogens. Mycobacterium tuberculosis (Mtb) harbors immune evasion mechanisms that impair DC responses and prevent optimal CD4 T cell immunity. The vaccine strain Mycobacterium bovis Bacille Calmette-Guérin (BCG) shares many of the immune evasion proteins utilized by Mtb, but the role of these proteins in DC and T cell responses elicited by BCG is poorly understood. We previously reported that the Mtb serine protease, Hip1, prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Additionally, M. tuberculosis promotes suboptimal antigen presentation in vitro and in vivo without detectable differences in the expression levels of costimulatory molecules when compared to BCG infected DCs(266). Interestingly, studies using a mutant M. tuberculosis strain lacking hip1 (discussed above) indicate that M. tuberculosis readily impairs DC costimulation and cytokine production to evade antigen-specific CD4 T-cell responses(107, 109) and a recent study demonstrated that BCG hip1 retains similar immune evasion functions(267). Taken together, the initiation of the adaptive immune response requires the participation of DCs, which themselves are readily infected and subverted by M. tuberculosis infection.…”
Section: Innate Immunity To M Tuberculosis Infectionmentioning
confidence: 99%
“…Additionally, M. tuberculosis promotes suboptimal antigen presentation in vitro and in vivo without detectable differences in the expression levels of costimulatory molecules when compared to BCG infected DCs(266). Interestingly, studies using a mutant M. tuberculosis strain lacking hip1 (discussed above) indicate that M. tuberculosis readily impairs DC costimulation and cytokine production to evade antigen-specific CD4 T-cell responses(107, 109) and a recent study demonstrated that BCG hip1 retains similar immune evasion functions(267). Taken together, the initiation of the adaptive immune response requires the participation of DCs, which themselves are readily infected and subverted by M. tuberculosis infection.…”
Section: Innate Immunity To M Tuberculosis Infectionmentioning
confidence: 99%
“…This may enable bystander cells to bypass pathogen-mediated inhibition of innate immune signaling in the directly infected cell ( Holmgren et al., 2017 ). Indeed, BCG retains immunomodulatory factors like Hip1 that negatively impact DC responses, including CD40 expression, leading to impaired control of Mtb after challenge ( Bizzell et al., 2018 ). Bystander effects have been observed previously in murine DCs infected with BCG: secretion of IL-12p40 was impaired in directly infected splenic CD11c + DCs from mice expressing a YFP-tagged IL-12p40 gene and bystander DCs were responsible for IL-12p40 secretion ( Rothfuchs et al., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…BCG has previously been shown to affect DC expression of Notch ligands ( Ito et al., 2009 ; Schaller et al., 2016 ) and TLR9 was reported to regulate granulomas induced by BCG via DLL4 ( Ito et al., 2009 ). Our lab has developed a knockout of hip1 in BCG (BCGΔ hip1 ) and found it to induce higher levels of IL-17 than wild type BCG ( Bizzell et al., 2018 ). Thus, it would be interesting to test whether DLL4 signaling is operant in the context of BCGΔ hip1 vaccination and whether engaging the CD40-DLL4 axis has an adjuvant effect on BCGΔ hip1 vaccination.…”
Section: Discussionmentioning
confidence: 99%